Beyond The Hype: a Real World Evaluation of Blockchain's Role in Democratizing Agri Food Systems - Dzreke, Simon Suwanzy (Economics and Business Journal (ECBIS), 2025)
Blockchain technology is touted for democratizing supply chains, but 30–40% of smallholder farmers are excluded from fair market participation due to information gaps and power imbalances. The first complete empirical examination of blockchain's capacity to empower disadvantaged farmers in Global South agri-food systems. The paper examines 15 large-scale implementations, including Kenyan coffee cooperatives and Indian dairy collectives, using a rigorous mixed-methods methodology. Technical scalability in resource-limited situations, governance structures that promote meaningful multi-stakeholder engagement, and quantifiable inclusion results for small-scale farmers are thoroughly examined. Comparative case study, agent-based adoption modeling, and quasi-experimental effect evaluation by Propensity Score matching reveal that blockchain's potential is not automatic nor inherent in eight nations. Techno-institutional synergy, not technological complexity, improves democracy, the research shows. Hybrid governance systems with farmer-controlled validator nodes and tokenized decision-making rights enhanced smallholder involvement by 58% and premium retention by 78% over corporate-controlled systems. However, technologically sophisticated deployments without institutional expertise frequently increase power concentration and exclusion. The blockchain viability index helps identify optimal deployment conditions for different commodities, empirical evidence challenges the idea that decentralization automatically promotes inclusion, and the inclusion-by-design framework helps policymakers embed equitable principles into decentralized agri-tech from the start. This study shows food system digitization practitioners and scholars that genuine democratization occurs when technology drives institutional transformation.